The Impact of Globalization on Industrial Relations in Nigeria (A Study of Selected Trade Unions) - OKWUISE, U. Young; UKWANDI, Sylvester; UGHERUGHE3, Joseph E. (International Journal of Psychosocial Rehabilitation, 2020)
This study was carried out to examine the “Impact of Globalisation on Industrial Relations in selected Trade Unions of Asaba. The instrument used for data collection was a questionnaire that was administered to 150 respondents and was fully retrieved. The statistical tool used for data analysis is the Analysis of Variance (ANOVA). Hypothesis testing was done using Linear Regression through SPSS version 2020 as it is appropriate for testing the results of the samples collected. The findings reveal that Globalisation within the scope of Economic Reforms, Trade Liberalisation, Economic Integration and Employees’ Job Relations has a strong positive impact on Industrial Relation among Trade Unions in Asaba, Delta State and Nigeria at large. It was concluded that enhance globalization and economic reforms will improve industrial relation activities of trade union in Nigeria. Based on the findings, it was therefore recommended that Members of the Trade Union in Asaba should wholeheartedly embrace Globalisation as the benefits are overwhelming. It was further recommended that Government should enforce Economic Reforms that will promote the activities of Trade Unions in Nigeria; Government and other stakeholders should promote Economic Integration and Industrial Relations and Government should enforce Economic Reforms that will promote the activities of Trade Unions in Nigeria.